Situations Referred to the International Criminal Court by the United Nations Security Council – “ad hoc Tribunalisation” of the Court and its Dangers - Lattmann, Tamás (Pécs journal of international and European law, 2016)
The study examines the possibility created by the Rome Statute, the founding and governing document of the International Criminal Court, according to which the United Nations Security Council has the option to refer situations to the court by a legally binding resolution acting under Chapter VII of the United Nations Charter. This is possible, regardless of the fact that the state concerned is a party to the Statue or not. According to the author’s conclusion – although only limited number of such situations could yet be examined – this legal possibility is currently far from being a success story. It is still important to emphasize that while it can be a really useful tool from the perspective of international politics, it may poses a serious threat to the future of the court.